2 Suicide prevention in Finland. (1st September 2016) - Partonen, Timo
Abstract : The story begins in the 1970s, when there was a Parliamentary Committee which had a focus of national health policy discussion on suicide and produced a report. In the early 1980s, the decision of the Minister of Social Affairs and Health started the planning of a nationwide suicide prevention program. The program had the research phase (1986–1991) which was coordinated by National Public Health Institute (KTL) and based on the situation analysis, detailed information, and original data on suicides. To this end, all the 1397 deaths from suicide in Finland during a period of 12 months were assessed with the psychological autopsy method which collected and analysed all the information available for each case. These data found that 93% suffered from a mental disorder and 88% had co-morbid conditions (more than one disorder at the same time), and that depressive disorders (59%), alcohol use disorders (43%) and personality disorders (31%) were the most prevalent mental disorders. The data-driven recommendations were thereafter locally applied for the implementation phase (1992–1996) which National Research and Development Centre for Welfare and Health (STAKES) coordinated. Professionals were mobilised across sectors and training was organised throughout the country. Work practices were developed and tailored to strengthen the implementation in some areas, guidebooks and good practices were produced, and the newsletter for feedback to the project was actively edited and circulated. During these years the decreasing trend in suicide mortality started, and according the internal and external evaluation the program managed A) to change work practices of professionals, especially in the primary health care, B) to change the way suicides were reported in the media, and C) to reduce suicide mortality (–11% from 1986 to 1996, or –16% from 1992 to 1996). The current situation is that the suicide mortality has thus far decreased by 51% from 1990 to 2014 (from 30.0 to 14.6 per 100, 000). Today, the work continues and we need to intensify our measures for suicide prevention, and the current activities are, e.g., KiVa school which includes 90% of all the comprehensive schools and targets against bullying, Good Hunting Mate! which provides psychosocial support targeted at members of hunting clubs, and Time Out! which provides psychosocial support targeted at men exempted from military or civil service. Current Care Guidelines by the Finnish Medical Society DUODECIM which in 2013–2015 have been published for bipolar disorder, borderline personality disorder, depression, eating disorders, insomnia, post-traumatic stress disorder, and schizophrenia give support to these activities. Further support was also provided by EUGENAS which in 2012–2014 exchanged the best practices for suicide prevention and produced the general and school-based guidelines, and the toolkits for the workplace and for media professionals.